1990
DOI: 10.1007/bf01044222
|View full text |Cite
|
Sign up to set email alerts
|

News media influences on public views of sentencing.

Abstract: Opinion polls in Canada, the United States, Great Britain, Australia, and elsewhere suggest that most members of the public would like their criminal courts to be harsher. Does media coverage of criminal sentencing contribute to a preference for harsher sentencing? Most people derive their information about sentencing from the news media, and content analyses of news stories in Canada and the United States demonstrate that crimes of violence and sentences of imprisonment are overrepresented. Moreover, the news… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 14 publications
7
81
0
4
Order By: Relevance
“…This is concerning as it is widely acknowledged that the media is a potent force and when used inappropriately can have detrimental consequences, leading to misconceptions and limited public knowledge (Kleck, 1996;Larsson et al, 2003;Roberts & Doobs, 1990). Thus the media play an important role in the formation and maintenance of weight stigmatization, shaping social consensus.…”
Section: Introductionmentioning
confidence: 99%
“…This is concerning as it is widely acknowledged that the media is a potent force and when used inappropriately can have detrimental consequences, leading to misconceptions and limited public knowledge (Kleck, 1996;Larsson et al, 2003;Roberts & Doobs, 1990). Thus the media play an important role in the formation and maintenance of weight stigmatization, shaping social consensus.…”
Section: Introductionmentioning
confidence: 99%
“…However, even if these effects are limited to public perceptions based on media reports, they still have important implications for criminal justice. Media reports influence legal proceedings and most people rely on the media for information about criminal justice (Hans & Dee, 1991;Robbennolt & Studebaker, 2003;Roberts & Doob, 1990). Further, given that animalistic descriptions of crime lead to a greater perceived risk of recidivism and more desire for custodial sentences, people exposed to these descriptions through the media may vote for harsher policies to address crime.…”
mentioning
confidence: 99%
“…Many studies have shown that the punitive attitudes of people decrease in severity the more they know about how the criminal justice system operates and about the alternatives for punishment (Balvig et al 2015;Gelb 2008;Roberts et al 2012). One possible reason for this is that the key source of information about such matters for ordinary people is the media, which often highlights exceptionally serious crime cases and in a way that prejudges the punishments handed out for crimes (Roberts and Doob 1990). It can also be assumed that the significance of the media as an information source regarding crime and punishment is heightened among those who are less educated (Rosenberger and Callanan 2011).…”
Section: Attitudes To Punishment and Knowledgementioning
confidence: 99%